PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS MASALAH UNTUK MENDAYAGUNAKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA SISWA SEKOLAH DASAR - Donna Avianty; Dyah Ayu Sulistyaning Cipta (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research is intended to describe the learning design using interactive multimedia with the content in accordance with the 2013 curriculum which emphasizes character education and encourages students to utilize higher-order thinking skills. This interactive learning multimedia is based on problems. The research method used is a development research with an instructional design model, ADDIE. The instrument used in this study is problem solving and questionnaire tests. The results showed that problem-based interactive multimedia designed to be able to utilize high-level thinking skills, as seen from the evaluation results of students with 86.2% completeness. The response process of students and teachers after the implementation of learning with interactive multimedia based on problems showed a very good response.